Pengaruh Corruption Perception Index dan Government Expenditure terhadap Foreign Direct Investment di ASEAN: Penelitian - Fikri Fadhillah; Dicky Iranto; Herlitah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the impact of the Corruption Perception Index (CPI) and government expenditure on foreign direct investment (FDI) in the ASEAN region. Utilizing secondary data from 2010-2023 sourced from UNCTAD, Transparency International, and the World Bank, this research applies a panel data regression method using the Random Effect Model (REM). The primary findings reveal contrasting outcomes. On a partial basis, the CPI was found to have no significant effect on FDI inflows. Conversely, government expenditure demonstrated a significant positive influence. This result implies that for foreign investors in the ASEAN region during the study period, government spending allocation was a more dominant consideration than the perception of corruption levels.